Study of Different Levels of Chlorantraniliprole 10%+Thiamethoxam 20% Mixture Against Major Insect-pests of Tomato - Patra, Sandip; Das, B. C.; Sarkar, S.; Dhar, P. P.; Samanta, A. (International Journal of Bio-resource and Stress Management, 2016)
Experiments were conducted at Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal, India to evaluate the efficacy of chlorantraniliprole 10%+thiamethoxam 20% @ 105, 128 and 150 g a.i. ha-1 along with other insecticides against major pests of tomato under field condition. Tomato crop was raised in Randomized Block Design during 2010−11 and 2011−12 crop seasons. One soil drench application of all the treatments was given at 10 days after transplanting @ 100 ml water plant-1 except λ-cyhalothrin 5 EC that was given as foliar spray at the same time with three replications. Observations of white fly, leaf miner and fruit borer were taken on 5th, 10th, 15th, 20th and 30th days after soil drench application. Yield was recorded separately for each treatment during both the seasons. The per cent reduction or increase (+) of parasitoids (Encarsia sp. and Apanteles sp.) were recorded only on 30th day after application. Results revealed that chlorantraniliprole 10%+thiamethoxam 20% mixture @ 150 g a.i. ha-1 gave excellent control of the two sucking pests, viz. leaf miner (5.09 and 5.75%) and white fly (0.50 and 0.41 scale) as well as of Helicoverpa armigera (0.46 and 0.61 larvae plant-1)for both the seasons. The yield increases were also significantly higher in Chlorantraniliprole 10%+thiamethoxam 20% mixture treatments as well as it showed remarkable specificity to two important natural enemies associated with tomato ecosystem.